2022
DOI: 10.3390/agronomy12020468
|View full text |Cite
|
Sign up to set email alerts
|

Consortia of Plant-Growth-Promoting Rhizobacteria Isolated from Halophytes Improve the Response of Swiss Chard to Soil Salinization

Abstract: Inadequate fertilization or the indiscriminate use of water with high salt concentrations have led to salinization of agricultural soils. In this context, biofertilization with plant-growth-promoting rhizobacteria (PGPR) is an environmentally benign strategy to stimulate plant growth, even under salt stress. Thus, we studied the use of isolated PGPR consortia from halophytes to enhance Swiss chard growth under saline conditions. Growth, photosynthetic apparatus response, nutrient status, pigment concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…Finally, it should be noted that other consortium strains, such as SMT38 and S110, have the capacity to produce ACC, which is capable of reducing the plant ethylene level [21], helping to overcome the potential growth inhibition induced by environmental stress factors [17,18,50], and therefore, preventing the level of ethylene from becoming growth inhibitory [65], which would allow greater development of the above-ground and belowground biomasses, which we were able to verify in our experiment.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Finally, it should be noted that other consortium strains, such as SMT38 and S110, have the capacity to produce ACC, which is capable of reducing the plant ethylene level [21], helping to overcome the potential growth inhibition induced by environmental stress factors [17,18,50], and therefore, preventing the level of ethylene from becoming growth inhibitory [65], which would allow greater development of the above-ground and belowground biomasses, which we were able to verify in our experiment.…”
Section: Discussionsupporting
confidence: 54%
“…The strains were named: Variovorax paradoxus (S110), Pseudomonas sp. (SDT3), Bacillus velezensis (SMT38), Pseudarthrobacter oxydans (SRT15), and Bacillus zhangzhouensis (HPJ40); for the isolation, characterization, identification, and conservation details, see our previous studies [18,[31][32][33][34]. Bacterial strains were selected because they had growth self-compatibility and exhibited high multi-stress resistance and a variety of complementary plant growth-promoting (PGP) properties, aspects that make them an ideal inoculum to be adapted to and employed in several agronomic management contexts and environmental conditions, thus being able to improve fertilization process efficiency in strawberry crops.…”
Section: Bacteria Strain Selection Characteristics and Inoculum Prepa...mentioning
confidence: 99%
See 2 more Smart Citations
“…Effective PGPR usage is constrained by a number of variables such as climate, water, soil characteristics, target species, etc. [24], and it is understood that these bacteria have growth conditions where they can be more or less effective, for example, it was found that some PGPR with increasing salinity, and with no relation with bacterial death, did not display their plant-growth promoting attributes [25]. Nonetheless, several studies have not only identified salt tolerate PGPR but also associated PGPR consortia specific for salt-stressed plants [21,23].…”
Section: Introductionmentioning
confidence: 99%